(untitled) (Swiss Medical Weekly, 2025)
INTRODUCTION: The COVID-19 pandemic has placed an enormous strain on the Swiss healthcare system. This study aims to assess the associations of the pandemic on Switzerland’s hospital resource use and in-hospital mortality among both COVID-19 and non-COVID-19 patients. METHODS: In this national cohort study, we analysed administrative claims data for medical inpatients from 1 January 2018 to 31 December 2021, using mixed-effects segmented regression models. Hospitalisations were divided into a control and an exposure group before (January 2018 to December 2019) and during (January 2020 to December 2021) the pandemic. Before the pandemic, the division into the groups was performed by random split. We investigated trends in in-hospital mortality, hospital length of stay, 30-day hospital readmission and facility discharge rates before and during the COVID-19 pandemic, to assess the pandemic’s association with both COVID-19 (exposure) and non-COVID-19 (control) patients. RESULTS: Among 1,510,836 included cases, 763,533 were hospitalised before and 747,303 during the COVID-19 pandemic including 61,151 with a diagnosis of COVID-19. Before the pandemic, there were no relevant changes in population-averaged in-hospital mortality in the control group and the randomly defined exposure group (−0.0263% and 0.0201% per month, respectively). During the pandemic, however, mortality showed an increase among COVID-19 patients by 0.3553% per month (95% confidence interval [CI]: 0.3546–0.3560; change in slope p <0.001; difference in slopes p <0.001), while there was no relevant change in the pandemic control group (slope: −0.0277% per month). Similarly, COVID-19 patients showed an increase in hospital length of stay and discharge to a post-acute care facility, while the trend for 30-day hospital readmission was decreased. CONCLUSION: In this study, we observed an association between the COVID-19 pandemic and hospital resource use in COVID-19 patients only, resulting in higher in-hospital mortality, longer lengths of hospital stay and more frequent facility discharges. No relevant differences were seen in the control group during both time periods.